MOTIVASI PEMBELAJARAN PADA SURAT AL-KAUSTAR : Studi Analisis Makna Yang Terkandung Pada Surat Al-Kaustar Ayat 1-3 - romlah, romlah; Sanuri, Sanuri (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2023)
Surat al-Kautsar contains motivation-motivation in life. This chapter consists of three verses, but many of the contents are very inspiring in social life. The first verse contains about humans being obliged to be grateful for all the blessings that Allah has given us, especially healthy favors, being given the opportunity to go to high school, being given sufficient sustenance, and still many other favors both material and non-material. Second, in this verse if humans want to achieve a successful life, be happy in the world and the hereafter, then humans must do two stages, namely: first, pray, namely building good communication with Allah, namely by facing and submitting to Allah SWT at least five times a day sincerely and continuously. , besides that humans are also obliged to build good communication with the community. Evidenced by real gait and sacrifice. For example: sharing knowledge with others, sharing sustenance to those in need, providing treatment for those who are sick, and at least providing support for a positive attitude. Furthermore, the last thing is when in the struggle there are definitely obstacles. Just ignore those who stop you or who don't like you, don't give up hope, just think of the obstacle as a constructive motivation to move forward. Because basically when you have advanced and superior achievements, automatically those who underestimate you will be cut off by themselves.